Community-Based Housekeeping Training for Women: Supporting Homestay Development in Desa Wisata Pintukota Kecil - Yulius, Kevin Gustian; Sianipar, Rosianna; Juliana, Juliana (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was designed to address the knowledge gap in hospitality and accommodation management among women in Desa Wisata Pintukota Kecil, a small island-based community based tourism destination in Lembeh Island, Bitung Municipality, North Sulawesi. As part of the community's recovery following a flood and landslide disaster in April 2024, the training aimed to equip local women with basic housekeeping knowledge to support homestay development and community-based tourism in a desa wisata. The activity was conducted on October 19, 2024, with 25 women participants. The method involved lectures and demonstrations focused on cleaning procedures, linen management, guest handling, and hygiene standards. Pretest and posttest evaluations using 15 multiple-choice questions revealed significant improvement in participants’ knowledge. Scores increased from 30–60% in the pretest to 88–100% in the posttest. The results show that the delivery method was effective and the training content was appropriate to the participants' context and needs. Women were identified as key actors in the potential growth of homestay-based tourism in the village. This initiative illustrates how targeted training can contribute to sustainable community empowerment and readiness for tourism engagement.